2003
DOI: 10.1002/ardp.200300732
|View full text |Cite
|
Sign up to set email alerts
|

1‐N‐Substituted Thiocarbamoyl‐3‐phenyl‐5‐thienyl‐2‐pyrazolines: Synthesis and Evaluation as MAO Inhibitors

Abstract: Twelve new 1-N-substituted thiocarbomoyl-3-phenyl-5-thienyl-2-pyrazoline derivatives were synthesized and evaluated their for antidepressant, anxiogenic and mammalian monoamine oxidase (MAO)-A and Binhibitory activities by in vivo and in vitro tests. MAO was isolated and purified from the mitochondrial pellet of bovine liver homogenates and human platelets. All of the new compounds inhibited the total MAO activity of liver homogenates and the inhibition was found to be time-dependent. Four compounds (3 i-3 l) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…The MAO inhibitors which have hydrazine and amine moiety such as isocarboxazid (Shader and Greenblatt, 1999), phenelzine (Urichuk, et al, 2000), and moclobemide (Ferigolo et al, 1998) show prominent antidepressant activity in animals and man. The antidepressant activity of 1-N-substituted thiocarbamoyl-3-phenyl-5-thienyl-2-pyrazolines was found to be similar to those of MAO inhibitors (Gökhan et al, 2003). Additionally, it has been shown that 1,3,5-triphenyl-2-pyrazolines (Prasad et al, 2005), 1-thiocarbamoyl-3,5-diphenyl-2-pyrazolines (Bilgin et al, 1993), bicyclic pyrazoline 8-thiocarbamoyl-7,8-diazabicyclo[4.3.0]non-6-ene derivatives (Palaska et al, 1996), and 3,5-difenil-2-pirazolines (Palaska et al, 2001) have antidepressant activity in forced swimming test.…”
Section: Introductionmentioning
confidence: 87%
“…The MAO inhibitors which have hydrazine and amine moiety such as isocarboxazid (Shader and Greenblatt, 1999), phenelzine (Urichuk, et al, 2000), and moclobemide (Ferigolo et al, 1998) show prominent antidepressant activity in animals and man. The antidepressant activity of 1-N-substituted thiocarbamoyl-3-phenyl-5-thienyl-2-pyrazolines was found to be similar to those of MAO inhibitors (Gökhan et al, 2003). Additionally, it has been shown that 1,3,5-triphenyl-2-pyrazolines (Prasad et al, 2005), 1-thiocarbamoyl-3,5-diphenyl-2-pyrazolines (Bilgin et al, 1993), bicyclic pyrazoline 8-thiocarbamoyl-7,8-diazabicyclo[4.3.0]non-6-ene derivatives (Palaska et al, 1996), and 3,5-difenil-2-pirazolines (Palaska et al, 2001) have antidepressant activity in forced swimming test.…”
Section: Introductionmentioning
confidence: 87%
“…NMR spectral analysis of compound 6 demonstrated that the regiochemical preference of the electron-withdrawing substitutent is toward to the N-portion of the dipole [6,7], affording a C-12-∆ 1 -pyrazoline derivative. Since pyrazoline derivatives have been demonstrated to possess many different biologically activities [8,9], compound 6 might be an intermediate from which active antibiotics could be made. …”
Section: The Epoxidation Of (9s)-911-o-isopropylidene-2'4''-o-bis(bmentioning
confidence: 99%
“…However, pyrazolines are still least explored compounds for anticonvulsant profile even, their function is quite stable [14]. In view of this and our continued interest in the synthesis of bioactive heterocyclic compounds with a stable fragment, it was thought of interest to synthesize some new pyrazolines starting from chalcone and semicarbazide [15].…”
Section: Introductionmentioning
confidence: 99%